Peculiarities of Identifying a Power-generating Single-shaft GTE Mathematical Model - Lyutikov, A.L. (Проблеми машинобудування, 2018)
The article proposes an approach to identifying a non-linear unit mathematical model (MM), with a detailed calculation of a turbine flow path to the level of blade rows on the D045 engine bench test results. It describes the choice of variable and controllable parameters as well as the ranges of their changes. The results of solving the identification problem showed the possibility of using the Optimum software for optimizing and identifying parameters and characteristics of power plants when identifying D045 GTE MMs. The use of the developed methodology for identifying GTE MMs that is based on bench test results, allows one to take into account the maximum number of variable variables and significantly reduce the complexity and time of this process. The analysis of the results shows that with significant deviations of GTE characteristics from design values, a large amount of a priori information is needed to solve the identification problem.